MONITORING OF AIR POLLUTION PRODUCED BY AIRCRAFT IN THE VICINITY OF AIRPORT - Synylo, Kateryna; Kazhan, Kateryna (Proceedings of National Aviation University, 2014)
Air pollution resulting from airport emissions and aircraft noise is a growing concern because of theexpansion of air traffic over the years. Monitoring (measurement) and modeling techniques enables the assessment ofhistorical, existing or future air pollution in the vicinities of airport.